Interaksionisme simbolik dalam penelitian lanskap budaya vernakular - Iwan Sudradjat; Irfan Sabarilah Hasim; Indah Widiastuti (ARTEKS : Jurnal Teknik Arsitektur, 2023)
Customary and traditional villages, also called vernacular cultural landscapes, are local settlement units whose inhabitants adhere to ancestral beliefs. It is important to conduct research on vernacular cultural landscapes in Indonesia, given the usual and concerning degradation of cultural landscapes. Different places have different cultures and different customary rules and habits. Each has its uniqueness and distinctiveness, so there is no one standardized approach or method that can be adapted to study the vernacular cultural landscape. Different places may require different research approaches or methods; even the same place if studied under a different topic or time frame, may also require a different approach or method. There are research approaches commonly used by the researcher of the vernacular cultural landscape, including phenomenology, narrative study, case study, grounded theory, and ethnography. This article will review one approach that can be an alternative for the researcher of the vernacular cultural landscape, namely Symbolic Interactionism. Symbolic Interactionism is an approach that can be effectively applied to study human groups, community life, and social interactions. Symbolic interactionism is able to reveal the relationships that occur naturally among members of the society, particularly the relationship between intangible symbols, rules, norms, and daily activities, with tangible things such as the formation of space, buildings, circulation, and other physical configurations.